Peran Teknologi Informasi Dalam Manajemen Pendidikan Islam - Kodir, Abdul; Suklani (El-Idare, 2024)
This research aims to understand the Role of Information Technology in Islamic Education Management. In the era of globalization and the advancement of information technology, the role of information technology in Islamic education management becomes increasingly significant. This article discusses the role of information technology in the evaluation and development of Islamic education curriculum. The research method used is literature study, with data collection from various sources such as scientific journals, books, and online articles. The results show that information technology enables structured collection and analysis of student learning outcome data, allowing for more accurate decision-making in curriculum improvement. Additionally, information technology also supports the development of curriculum that is responsive to changes in society and the education world, as well as the formulation of inclusive and diverse curriculum. However, there are challenges such as understanding and skills in utilizing information technology that need to be overcome. Therefore, the integration of information technology in the evaluation and development of Islamic education curriculum requires commitment and joint efforts from all relevant parties to improve the quality of Islamic education in this digital era.